Ciphertext-only cryptanalysis of Hagelin M-209 pins and lugs. Issue 2 (3rd March 2016) - Lasry, George; Kopal, Nils; Wacker, Arno
ABSTRACT: The Hagelin M-209 was a mechanical encryption device used by the U.S. Army during World War II and the Korean War, as well as by other armies and in embassy settings. In this article, the authors present a four-stage hillclimbing algorithm for recovering the full key settings from ciphertext only. The first two stages are based on a divide-and-conquer approach developed by Geoff Sullivan. In the current performance evaluation, the authors show that their method is able to recover key settings from messages as short as 750 letters, compared to 2, 000 – 2, 500 letters with prior methods. With this method, they solved several M-209 ciphertext-only challenges, including the final exercises in W. Barker's 1977 book, Cryptanalysis of the Hagelin Cryptograph .